A CRITICAL GAZE AT PSYCHOLOGY - Stevens, Garth (PINS-Psychology in Society, 2025)
Hook, D (2007) Foucault, psychology and the analytics of power. Houndmills: Palgrave Macmillan. ISBN-13 978-0-230-00819-9 hbk. Pages xii + 301. Foucault, psychology and the analytics of power provides a compelling critique of the established and taken for granted co-ordinates of modern psychology as a discipline and set of practices. It provides a much needed injection of criticality into a discipline and profession that has for far too long been complacent about its historically conservative origins, functions and effects, and which continues in the main to labour under the illusion that psychology is merely a discipline premised on humanistic forms of altruism in the search for “truth”. Written by Derek Hook, a prominent critical psychology scholar, this collection of essays begins with the promise of stripping away some of these illusory features of modern psychology. Not only does it deliver on this promise amply by highlighting psychology’s development as a socio-medical science alongside the evolution of relations of power from sovereignty, to humanistic reformism, to more insidious disciplinary forms of power, but spells out how psychology has come to epitomize certain technologies of self-regulation and a form of moral orthopaedics that in fact contributes to the development of a docile psychological subject. It then extends on this initial promise and examines the critical value of Foucault’s work in psychology and the social sciences more broadly today.